Liquidity and Asset Prices: How Strong Are the Linkages? - Christian Dreger; Jürgen Wolters (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The appropriate design of monetary policy in integrated financial markets is one of the most challenging areas for central banks. One hot topic is whether the rise in liquidity in recent years has contributed to the formation of price bubbles in asset markets. If strong linkages exist, the inclusion of asset prices in the monetary policy rule can eventually limit speculative runs and negative effects on the real economy in the future. We explore the impacts of liquidity shocks on real share and house prices and the influence of wealth prices on liquidity. VAR models are specified for the US and the euro area. To control for international spillovers, global VARs are also considered. Differences in the results can provide a measure on the impact of financial market integration. The specifications point to some impact of liquidity shocks on house prices, while asset prices are not affected.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: E44; G10; C32; C52; 330; Liquidity shocks; asset prices; GVAR analysis; monetary policy